2018
DOI: 10.1038/s41598-018-24906-x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular higher-order aberrations and axial eye growth in young Hong Kong children

Abstract: This retrospective longitudinal analysis aimed to investigate the association between ocular higher-order aberrations (HOAs) and axial eye growth in Hong Kong children. Measures of axial length and ocular HOAs under cycloplegia were obtained annually over a two-year period from 137 subjects aged 8.8 ± 1.4 years with mean spherical equivalent refraction of −2.04 ± 2.38 D. A significant negative association was observed between the RMS of total HOAs and axial eye growth (P = 0.03), after adjusting for other sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 80 publications
(86 reference statements)
2
65
7
1
Order By: Relevance
“…The relationship between HOAs and axial eye growth has recently been investigated in spectacle‐wearing children . Hiraoka et al indicated that higher levels of vertical coma (Z31) and spherical aberration (Z40) were correlated with slower axial eye growth, whereas Lau et al demonstrated that oblique trefoil (Z33) and spherical aberration (Z40) were associated with slower axial elongation, after accounting for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between HOAs and axial eye growth has recently been investigated in spectacle‐wearing children . Hiraoka et al indicated that higher levels of vertical coma (Z31) and spherical aberration (Z40) were correlated with slower axial eye growth, whereas Lau et al demonstrated that oblique trefoil (Z33) and spherical aberration (Z40) were associated with slower axial elongation, after accounting for confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of experimentally induced ametropia in animal models suggest that the changes in HOAs associated with refractive error development are predominated by an increase in the asymmetric aberrations of the third radial order . Eyes with experimentally acquired ametropia show increased magnitudes of coma and trefoil, therefore such asymmetric HOAs may provide a signal that influences ocular growth, which has been hypothesised based on longitudinal data from human studies . Additionally, Wildsoet and Schmid demonstrated that the chick eye is able to modulate ocular growth on the basis of optical vergence, hence it may be possible that the eye uses vergence cues from these asymmetric HOAs to influence eye growth.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…Lau et al reported higher spherical aberration and HOA RMS values in Hong Kong children who underwent slower axial eye growth, after controlling for factors known to affect axial elongation such as age, gender, and baseline refractive error. Reduced axial elongation was also associated with less positive oblique trefoil (Z33), more positive primary trefoil (Z33) and more positive spherical aberration (Z40), with each 0.1 μm increment of each term associated with ~0.13, 0.11 and 0.11 mm difference in axial eye growth per year, respectively . Interestingly, given the partial compensatory effect of anterior corneal HOAs by internal HOAs, Hiraoka et al found that myopia progression and axial elongation correlate independently with many corneal HOAs, and more strongly than ocular HOAs in Japanese children.…”
Section: Hoas and Refractive Errormentioning
confidence: 99%
See 2 more Smart Citations